The Struggle of Jihadist’s Ideology in Hikayah Wahabiyyah - Cahya Buana; Ahmadi Usman (Institut Agama Islam Negeri Madura, 2019)
Hikayah Wahabiyyah was banned (2013) in Saudi Arabia because it was considered to undermine the honor of religion, institutions and state stability. Hikāyah Wahabiyyah describes the struggle of the ideology of a Wahabi who wants to escape from a total domination (herrschaft) that has eliminated the freedom and clarity of modern human thinking. This study aims to reveal the struggle of a Wahabi jihadist as reflected through internal elements of the Hikayah Wahabiyah. To uncover this ideological struggle, I use the ideological criticism approach to the intrinsic elements of the novel. Based on the analysis results are summarized, that (1) the word “jihadis” in this novel is interpreted as a kinayah which has two meanings, haqiqi and majazi (real and figurative). The meaning of haqīqi is those who strive in jihad through the path of war, while the meaning of the majazi is those who strive to maintain their ideological beliefs. (2) the intrinsic elements of literature built by the author in general illustrate the ideological struggle of a mutadayyin (follower of the Wahhabi ideology) who turns into a muntakis (someone who escapes from Wahabi ideology).